Effect of evacuation and displacement on the association between flooding and mental health outcomes: a cross-sectional analysis of UK survey data. Issue 4 (July 2017) - Munro, Alice; Kovats, R Sari; Rubin, G James; Waite, Thomas David; Bone, Angie; Armstrong, Ben; ,
Summary: Background: Extensive flooding occurred during the winter of 2013–14 in England. Previous studies have shown that flooding affects mental health. Using data from the 2013–14 Public Health England National Study of Flooding and Health, we compared the prevalence of symptoms of depression, anxiety, and post-traumatic stress disorder between participants displaced by flooding and those flooded, but not displaced, 1 year after flooding. Methods: In this multivariable ordinal regression analysis, we collected data from a cross-sectional survey collected 1 year after the flooding event from flood-affected postcodes in five counties in England. The analysis was restricted to individuals whose homes were flooded (n=622) to analyse displacement due to flooding. The primary outcome measures were depression (measured by the PHQ-2 depression scale) and anxiety (measured by the two-item Generalised Anxiety Disorder [GAD]-2 anxiety scale), and post-traumatic stress disorder (measured by the Post-Traumatic Stress Disorder Checklist [PCL]-6 scale). We adjusted analyses for recorded potential confounders. We also analysed duration of displacement and amount of warning received. Findings: People who were displaced from their homes were significantly more likely to have higher scores on each scale; odds ratio (OR) for depression 1·95 (95% CI 1·30–2·93), for anxiety 1·66 (1·12–2·46), and for post-traumatic stress disorder 1·70 (1·17–2·48) than people who were not displaced. The increased risk of depression was significant even after adjustment for severity of flooding. Scores for depression and post-traumatic stress disorder were higher in people who were displaced and reported receiving no warning than those who had received a warning more than 12 h in advance of flooding (p=0·04 for depression, p=0·01 for post-traumatic stress disorder), although the difference in anxiety scores was not significant. Interpretation: Displacement after flooding was associated with higher reported symptoms of depression, anxiety, and post-traumatic stress disorder 1 year after flooding. The amount of warning received showed evidence of being protective against symptoms of the three mental illnesses studied, and the severity of flooding might be the reason for some, but not all, of the differences between the groups. Funding: National Institute for Health Research Health Protection Research Units (HPRU) in Emergency Preparedness and Response at King's College London, Environmental Change and Health at the London School of Hygiene and Tropical Medicine, and Evaluation of Interventions at the University of Bristol, Public Health England.